The Efficiency of Repeated Debulking Surgery for Recurrent Ovarian Cancer - Norpulatov J; Allamova Sh.M; Tursunova N.I (Genius Journals, 2022)
to estimate the effectiveness of repeated debulking surgeries and identify factors that determine the survival of patients with combined treatment of ovarian cancer recurrence.
Keywords: ovarian cancer relapse; repeated; surgeries